2008
DOI: 10.1016/j.annepidem.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Associations Between Body Mass Index and DSM-IV Mood and Anxiety Disorders: Results from the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: PURPOSE-The purpose of this study is to examine gender differences in associations between body mass index (BMI) and affective disorders.METHODS-We used logistic regression to examine the effects of BMI and gender on DSM-IV mood and anxiety disorders in a sample of 40,790 adults.RESULTS-Obesity (BMI ≥ 30.0) was associated with increased risk for any mood disorder, major depressive disorder, and dysthymic disorder, in both men and women (odds ratios [ORs], 1.35-1.88). Risk of bipolar I and II disorders was elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 48 publications
12
118
2
6
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men. [27][28][29] This could be explained by the differences in study population, measurements for psychiatric disorders or potential confounding variables included in the analyses in these studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men. [27][28][29] This could be explained by the differences in study population, measurements for psychiatric disorders or potential confounding variables included in the analyses in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…3 A growing body of evidence has shown that obesity, highly prevalent and increasing in the United States and worldwide, [4][5][6] is associated with an increased risk of developing psychiatric disorders. [7][8][9][10][11][12][13][14][15] However, most of the earlier studies failed to evaluate the effects of obesity-related comorbidities (ORCs), lifestyle factors (such as smoking, alcohol drinking and physical activity) or other psychosocial factors (such as general health status, emotional support and life satisfaction) on mental health simultaneously, although these factors also affect mental health status 13,[16][17][18][19] or are associated with mental disorders. 16,[20][21][22][23][24][25] On the other hand, some other studies have found no relationship 26 or an inverse association of overweight/obesity with mental disorders in men.…”
Section: Introductionmentioning
confidence: 99%
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results are presented by studies on the association between obesity and social anxiety (3,27,31,32). The frequency of social anxiety in obesity has been found to be 59% (9).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in our study it was found that, besides depression, increase of social anxiety level is a predictor for the development of obesity. Barry et al found a significant association between social anxiety and obesity and specified that this association occurred as obese people anticipate being negatively evaluated based on weight (27).…”
Section: Discussionmentioning
confidence: 99%